THE USE OF MODERN TECHNOLOGY IN TEACHING ENGLISH - Halilova, Himoyat (Журнал иностранных языков и лингвистики, 2021)
The application of modern technology represents a significant advance in contemporary English language teaching methods. Indeed, Mohammad Reza Ahmadi (2018) maintains that electronic teaching programs have become the predominant preference of instructors since they arguably boost positive student engagement with teachers and incentivize overall English language learning.